Impact of soybean stover- and pine needle-derived biochars on Pb and As mobility, microbial community, and carbon stability in a contaminated agricultural soil. (15th January 2016) - Ahmad, Mahtab; Ok, Yong Sik; Kim, Byung-Yong; Ahn, Jae-Hyung; Lee, Young Han; Zhang, Ming; Moon, Deok Hyun; Al-Wabel, Mohammad I.; Lee, Sang Soo
Abstract: Biochar is gaining attention as a potential soil amendment to remediate and revitalize the contaminated soils. Simultaneous effects of biochar on metals mobility, microbial abundance, bacterial diversity and carbon storage in soil are scarcely addressed. This study assessed the effect of biochars on metal mobility, microbial abundance, bacterial community, and carbon storage in an agricultural soil contaminated with heavy metals. Biochars derived from soybean stover at 300 and 700 °C (S-BC300 and S-BC700, respectively) and pine needles at the same temperatures (P-BC300 and P-BC700, respectively) were used. A maximum reduction of Pb mobility by 95% was observed from a soil treated with S-BC700, associated with precipitation of chloropyromorphite and hydroxylpyromorphite. In contrast, As was desorbed from soil particles because of P competition. The abundance of Gram-positive and negative bacteria, fungi, actinomycetes, and arbuscular mycorrhizal fungi increased in the soils treated with biochar produced at 300 °C, possibly due to the high dissolved organic and active organic carbons. Microbial abundance in the soils treated with S-BC700 and P-BC700 was constant due to the existence of fixed or non-labile carbon. Changes to bacterial communities in the biochar-treated soils depended on feedstock type and pyrolysis temperature. Actinobacteria substantially increased whereas Acidobacteria and Chloroflexi decreased in the biochar-treated soils. The non-labile carbon fraction was ∼25 fold higher in the biochar-treated soil than the control soil, indicating long-term carbon storage. Highlights: Pb immobilized while As mobilized in a contaminated soil amended with biochar. Microbial concentrations increased in soils amended with biochars produced at 300 °C. Biochar feedstock type and pyrolysis temperature influenced soil microbial diversity. Non-labile C fraction increased in biochar amended soil indicating C sequestration.